The Role of Brand Image in Enhancing Repurchase Intention of Low-Cost Carrier Airlines - Olfebri Olfebri; Yuliantini Yuliantini; Aang Gunawan; Primadi Candra Susanto; Nasrullah Nasrullah; Danang Darunanto (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the impact of service quality, on-time performance, and promotions on the repurchase intention of low-cost carrier (LCC) users, both directly and indirectly, through brand image as a mediating variable. Methodology/approach: A qualitative descriptive approach with a literature review was used. Data were collected from internationally indexed articles in databases such as Scopus, Web of Science, and Google Scholar. The selected literature was analyzed using data reduction techniques, data presentation in matrix form, and comparative synthesis to identify patterns and differences between the relevant studies. Results: The results show that service quality, on-time performance, and promotions influence repurchase intention among LCC users, either directly or through brand image. Brand image has been proven to act as a mediating variable that strengthens the relationship between operational and marketing factors and the repeat purchase. Conclusions: This study confirms that the competitive advantage of LCC is determined not only by price but also by brand perception built through user service experiences. Brand image plays a significant role in enhancing repurchase intentions. Contribution: This study contributes to the theoretical understanding of consumer behavior in the airline industry, particularly in explaining the role of brand image as a mediating mechanism between service quality, time performance, promotions, and repurchase intention. Limitation: The limitation of this study lies in the use of a literature review method, which does not involve direct empirical testing of primary data from airline passenger.